2017
DOI: 10.2147/dddt.s141031
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of lidocaine- and prilocaine-coloaded nanoparticulate drug delivery systems for topical anesthetic analgesic therapy: a comparison between solid lipid nanoparticles and nanostructured lipid carriers

Abstract: PurposeTopical anesthesia analgesic therapy has diverse applicability in solving the barrier properties of skin and unfavorable physicochemical properties of drugs. Lidocaine (LID) combined with prilocaine (PRI) has been used as a topical preparation for dermal anesthesia for treatment of conditions such as paresthesia.Materials and methodsIn this study, for combination anesthesia and overcoming the drawbacks of LID and PRI, respectively, LID- and PRI-loaded solid lipid nanoparticles (SLNs) and nanostructured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 41 publications
3
23
0
2
Order By: Relevance
“…The components of the NLC formulation have similar lipophilicity as the skin, so they have good miscibility with the skin lipids, and this can cause greater penetration [37]. Our results are in good agreement with other studies, which revealed that lipid nanocarriers can improve penetration and effectiveness of encapsulated lidocaine [2,5,38,39]. The high penetration rate of LID through the epidermis predicts the fast accumulation of the drug in the dermis, which is the site of action for local anesthetics.…”
Section: Results Of In Vitro Release and Ex Vivo Permeation Studiessupporting
confidence: 88%
“…The components of the NLC formulation have similar lipophilicity as the skin, so they have good miscibility with the skin lipids, and this can cause greater penetration [37]. Our results are in good agreement with other studies, which revealed that lipid nanocarriers can improve penetration and effectiveness of encapsulated lidocaine [2,5,38,39]. The high penetration rate of LID through the epidermis predicts the fast accumulation of the drug in the dermis, which is the site of action for local anesthetics.…”
Section: Results Of In Vitro Release and Ex Vivo Permeation Studiessupporting
confidence: 88%
“…Based on the results of the RA, these points have been investigated in this research. Our results are in good agreement with other studies, which revealed that lipid nanocarriers can improve penetration and effectiveness of encapsulated LID [91,[93][94][95].…”
Section: Initial Risk Assessmentsupporting
confidence: 93%
“…Additionally, the safety behavior observed for XAN-NLC/LDC-PLC hydrogel was predictable, since NLC formulations were previously described as noncytotoxic for 3T3 and HaCat cells. 36,[46][47][48] Finally, the anesthesia duration was determined through tail-flick assay in mice. XAN-NLC/LDC-PLC exhibited an anesthetic effect two times higher than the control hydrogel (XAN/LDC-PLC) and four times higher than the commercially available cream.…”
Section: Discussionmentioning
confidence: 99%
“…Since pure XAN hydrogel is widely known as noncytotoxic, even after 21 days of analysis, 35 samples is a result of the well-known intrinsic cytotoxicity of LA. 36 Last but not least, the anesthetic effect of the XAN-based hydrogels was assessed by the tail-flick test in mice (n=5). Figure 6 shows the %MPE and total anesthesia, given by the area under the curve for XAN-NLC/LDC-PLC (~505), XAN/ LDC-PLC (~238) hydrogels and the eutectic mixture of LDC-PLC cream (~76).…”
Section: Bioassaysmentioning
confidence: 99%